The Blending of EPDM/NR with Maleic Anhydride as Compatibilizer: Comparing the Effect of Accelerators on Cure Characteristic and Mechanical Properties - Hesty Eka Mayasari; Ike Setyorini; Arum Yuniari (Universitas Gadjah Mada, 2019)
The blending of ethylene propylene diene monomer/natural rubber (EPDM/NR) needs much attention because of their incompatibility. In this work, the influence of accelerator type on cure characteristics and mechanical properties of 60/40 EPDM/NR blend was investigated. The compounds were prepared by controlling the migration of curative and using maleic anhydride as the compatibilizer. Three types of accelerators were studied: 2,2-dithiobis(benzothiazole) (MBTS), the combination of MBTS and tetramethyl thiuram disulfide (TMTD), and n-tert-butyl-2-benzothiazolesulfenamide (TBBS). The cure characteristic, mechanical properties, and morphology of the composites had been investigated by rheometer, tensile testing machine, hardness durometer and scanning electron microscope (SEM). Blending of EPDM/NR with various accelerator gave different composite characteristics. MBTS, used in single or binary accelerator system, provided good mechanical properties. TBBS gave the longest scorch time, the lowest crosslink density and poor mechanical properties, except tear strength. Binary accelerator, MBTS/TMTD, provided the lowest processing time and the highest cure rate, but not significantly different from MBTS. Binary accelerator gives the best aging resistance and compatibility blend. These results correspond well with SEM micrograph. From the study, it can be concluded that binary accelerator system was the proper accelerator for EPDM/NR blend.